PERAN PERPIPAAN AIR LIMBAH DOMESTIK (STUDI KASUS DI DESA KEBON AYU) - YOHANES MARDIANTO MAWAN METE; BAGUS WIDHI DHARMA S.; BAIQ RENI SARI DEWI (SOSIAL SAINS DAN TEKNOLOGI, 2023)
Pipeline networks and wastewater treatment processes can be optimized by planning with careful calculations in accordance with technical provisions regarding the flow of wastewater in pipes so that sediment and blockages do not occur. The purpose of this study was to determine the debit of household or domestic wastewater, the diameter of the wastewater pipes, and the effective piping system. This study uses a quantitative descriptive method. The data needed include topographical data, population, average water consumption, location map, and field elevation. The results showed that the discharge of wastewater in the village of Kebon Ayu had a population of 0.00189 m3/s with a population of 1685 people. With a minimum channel slope of 0.1%. The maximum diameter of the wastewater pipe for a discharge of 0.00189 m3/sec is 7.03 inches and the minimum diameter for a wastewater discharge of 0.00015 m3/sec is 2.99 inches. Waste water in the village of Kebon Ayu residents is channeled by piping using a branched pipe network system.